TRADITIONS AS A RESOURCE FOR THE DEVELOPMENT OF MOUNTAINOUS TERRITORIES OF DAGESTAN - Magomedhanov, Magomedhan Magomedovic; Sadovoj, Aleksandr Nikolaevic; Magdilov, Mazid Magdievic (History, Archeology and Ethnography of the Caucasus, 2024)
The article examines the maintenance of ethno-cultural traditions aimed at preserving and enhancing the socio-economic and demographic vitality of the mountainous regions of Dagestan. It highlights the following points: a) during the imperial era, rural communities and their self-governing institutions were formally recognized (Regulations of April 26, 1868), thereby safeguarding traditional systems of governance, land tenure, land use, education, and legal proceedings. The onset of capitalist relations in the mountainous regions during the late 19th and early 20th centuries actually stimulated the development, rather than displacement, of traditional economic structures. This collective effort contributed to maintaining the region’s stability and prosperity; b) in the Soviet era, the administrative-territorial organization of the Dagestan Autonomous Soviet Socialist Republic (DASSR) saw the implementation of socialization measures, including nationalization and the distribution of communal (khIarim), private (mulk), and mosque-administered (waqf) lands to collective farms, with due consideration given to the boundaries of rural communities. Following the Second World War (1941-1945), collective farms gained prominence; c) the processes of perestroika and post-Soviet periods witnessed the privatization of collective farm assets, including administrative and auxiliary buildings in mountainous areas and lands designated for transhumance, as well as the transfer of alpine and winter pastures to new owners. Traditional rural self-governing institutions were gradually marginalized in favor of “economic entities.” Despite receiving state support through federal and regional programs, these changes led to the decline of mountain economies and subsequent depopulation of these regions. The article underscores that the ethno-cultural landscape of mountainous areas, which largely remain outside the realm of modern mountain economy technologies in Dagestan, is shaped not only by physical-geographical and economic factors but also by the inherent way of life in these regions, as understood through socio-demographic and ethno-cultural lenses.